2005
DOI: 10.1136/jmg.2004.030296
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary breast/ovarian and colorectal cancer genetics knowledge in a national sample of US physicians

Abstract: Background: Clinically relevant genetics knowledge is essential for appropriate assessment and management of inherited cancer risk, and for effective communication with patients. This national physician survey assessed knowledge regarding basic cancer genetics concepts early in the process of introduction of predictive genetic testing for breast/ovarian and hereditary non-polyposis colorectal cancer (HNPCC) syndromes. Methods: A stratified random sample was selected from the American Medical Association Master… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
127
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 33 publications
7
127
2
Order By: Relevance
“…In that survey, respondents who had received genetics training in medical school were almost twice as likely to have ever ordered a genetic test compared to those without such training (OR 1.80, 95% CI: 1.34 -2.43; p= 0.001). Several studies have reported limited physician knowledge of genetics, albeit higher in younger physicians and in disciplines more closely affiliated with genetics, namely pediatrics and obstetrics/gynecology 12,15,16 . Similarly, we found that time since graduation is linked to perceived inadequacy of genetics training, and perceived knowledge is linked to test ordering behaviors 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In that survey, respondents who had received genetics training in medical school were almost twice as likely to have ever ordered a genetic test compared to those without such training (OR 1.80, 95% CI: 1.34 -2.43; p= 0.001). Several studies have reported limited physician knowledge of genetics, albeit higher in younger physicians and in disciplines more closely affiliated with genetics, namely pediatrics and obstetrics/gynecology 12,15,16 . Similarly, we found that time since graduation is linked to perceived inadequacy of genetics training, and perceived knowledge is linked to test ordering behaviors 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Given physicians' limited knowledge of genetics and genetic testing [12][13][14][15][16] , prior to using the test physicians completed four online educational modules on genomic risk profiling developed by Navigenics. The modules provide an overview of the science underlying testing (genome-wide association studies), and the application of test results in preventive care 18 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,[73][74][75] Much of this genetic information has evolved over the past decade, and is unfamiliar even to physicians whose specialty interests regularly bring them into contact with patients in need of this advice. 76 This speaks to a need for continuing education for non-genetics health care providers, and for active collaborations and referrals between providers and genetics professionals.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45][46] Researchers investigating HCPs' genetic competence, practice and/ or behaviour, have mainly collected data via surveys and questionnaires where HCPs self-report information. 27,37,[43][44][45][46][47][48][49][50][51] There are limitations in these types of studies regarding the validity of the data obtained in terms of how much they reflect the actual situation. Van Riel et al 27 explored the knowledge and attitudes of medical specialists on BRCA testing and their referral pattern to genetic services through questionnaires, suggesting a substantial proportion of patients at risk of hereditary breast cancer were not being referred.…”
Section: Discussionmentioning
confidence: 99%